Precision Mechanical Measurement Using the Levitation Mass Method (LMM) - Yusaku Fujii; Tao Jin; Koichi Maru (Institut Teknologi Bandung, 2011)
The present status and the future prospects of a method for precision mass and force measurement, the levitation mass method (LMM), are reviewed. The LMM has been proposed and improved by the authors. In the LMM, the inertial force of a mass levitated using a pneumatic linear bearing is used as the reference force applied to the objects under test, such as force transducers, materials or structures. The inertial force of the levitated mass is measured using an optical interferometer. The three typical applications of the LMM, i.e. the dynamic force calibration, the micro force material tester and the space scale, are reviewed in this paper.